IMPLEMENTATION OF CRIMINAL PUNISHMENTS FOR POLITICAL PARTIES - RIFANDHANA, RADITYA FEDA (Jurnal Independent, 2022)
AbstractÂ Indonesia is a state of law, the law consists of general and special laws, so the law is used for a deterrent effect for those who violate the law, for special laws, the punishment is heavier because it is related to corruption, the corruption that can be related to political parties. In this writing, normative research is used, namely reviewing the legislation. so that normative research can help complete this research, and can find out the application of criminal penalties for corruption for political parties, so that corruption can be prevented and eradicated from political parties.